Short-Selling Bans around the World: Evidence from the 2007-09 Crisis - Alessandro Beber; Marco Pagano (Tinbergen Institute, 2010)
Most stock exchange regulators around the world reacted to the 2007-2009 crisis byimposing bans or regulatory constraints on short-selling. Short-selling restrictions wereimposed and lifted at different dates in different countries, often applied to different sets ofstocks and featured different degrees of stringency. We exploit this considerable variationin short-sales regimes to identify their effects with panel data techniques, and find that bans(i) were detrimental for liquidity, especially for stocks with small market capitalization,high volatility and no listed options; (ii) slowed down price discovery, especially in bearmarket phases, and (iii) failed to support stock prices, except possibly for U.S. financialstocks.
Keywords: G01; G12; G14; G18; 330; short selling; ban; crisis; liquidity; price discovery; Internationaler Finanzmarkt; Wertpapierhandel; Leerverkauf; Kapitaleinkommen; Bankenliquidität; Finanzkrise; Welt